2017
DOI: 10.1016/j.ijid.2016.11.423
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric multidrug-resistant tuberculosis clinical trials: challenges and opportunities

Abstract: Objectives On June 17, 2016, RESIST-TB, IMPAACT, Vital Strategies, and New Ventures jointly hosted the Pediatric Multidrug Resistant Tuberculosis Clinical Trials Landscape Meeting in Arlington, VA. The meeting provided updates on current multidrug-resistant tuberculosis (MDR-TB) trials targeting pediatric populations and adult trials that included pediatric patients. Methods A series of presentations were given that discussed site capacity needs, community engagement, and additional interventions necessary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…36 There is an unmet need for TB treatment trials recruiting children and adolescents. 37 Urgent questions address efficacy, toxicity and prophylactic treatment of contacts to MDR TB. 37 A study from Tblisi, Georgia, described pulmonary surgery in 137 patients half with MDR/XDR TB.…”
Section: Tb Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…36 There is an unmet need for TB treatment trials recruiting children and adolescents. 37 Urgent questions address efficacy, toxicity and prophylactic treatment of contacts to MDR TB. 37 A study from Tblisi, Georgia, described pulmonary surgery in 137 patients half with MDR/XDR TB.…”
Section: Tb Treatmentmentioning
confidence: 99%
“…37 Urgent questions address efficacy, toxicity and prophylactic treatment of contacts to MDR TB. 37 A study from Tblisi, Georgia, described pulmonary surgery in 137 patients half with MDR/XDR TB. 38 Whereas it was too early to describe outcomes in terms of mortality, the study found that "from the 98% of DS-TB cases presenting cavities or tuberculomas and considered bacteriology cured according to WHO definitions, 56% were AFB positive from samples from the surgical specimens".…”
Section: Tb Treatmentmentioning
confidence: 99%
“…[2][3][4][5] Trials of multidrug-resistant tuberculosis (MDR-TB; defined as mycobacteria resistant to isoniazid and rifampicin) are necessary in children to confirm drug safety, inform appropriate dosing, and optimise treatment strategies and outcomes for children. [6][7][8] Literature on community engagement emphasises that it consists of a complex set of locally adaptive processes to foster active participation in research-related decisions through dialogue, multidirectionality and co-ownership-all of which are challenging to implement optimally, especially in paediatric populations. 3,[9][10][11] In addition, paediatric MDR-TB trials impose a unique combination of three additional complexities on community engagement:…”
mentioning
confidence: 99%
“…There is a need to reach global consensus on the optimal design of MDR-TB clinical trials. [5][6][7][8] Previous and some ongoing trials rely on large sample sizes and are of lengthy followup duration in order to produce convincing evidence base of efficacy of new TB drugs and regimens. Reducing large sample sizes and trialling more than one new TB drug in the same trial using the multi-arm, multi-stage (MAMS) design will allow maintaining flexibility to adapt to other data becoming available while trial in progress 6 .…”
mentioning
confidence: 99%
“…Several barriers exist in conduct RCTs in children and these need to be overcome. 7 Efficacy and safety from adult trials can be expanded to children after pilot pharmacokinetic and bioavailability studies. With the growing burden of MDR-TB in children and in HIVco-infected patients a range of trials are required to define optimal regimens for MDR-TB treatment and these will face the conventional issues of pharmacokinetics of new TB drugs; TB/HIV drug interactions, toxicity, and selection of the appropriate pediatric study population, case definition for TB in the absence of microbiological confirmation, and new strategies for integrating children into adult tuberculosis trials …”
mentioning
confidence: 99%